Expanding the discourse: a critical analysis of hip-hop feminism in the era of globalization - Ling, Xi; Chen, Yuanyuan; Zhu, Xuanmin (Frontiers in Sociology, 2025)
The emergence of hip-hop feminism as a cultural, intellectual, and political movement has captured global attention in recent years, highlighting its significance in contemporary discourse. This review aims to re-examine the definition of hip-hop feminism, particularly in the context of globalization and digital media, and to explore its impact on challenging gender stereotypes and enhancing women’s discursive power. Through a critical review and analysis of existing literature, this review reveals the deficiencies in the definition of hip-hop feminism and proposes updated and expanded definitions that more comprehensively reflect its global and cross-cultural dimensions. The findings suggest that hip-hop feminism encompasses a broader spectrum of activities and influences. It not only addresses the lives and perceptions of black women but also extends to performative and ethnographic studies, engages actively in digital platforms such as blogs and online communities, and facilitates new avenues for women’s political engagement and social activism on a global scale. This review poses critical questions to address potential gaps in the existing literature, thereby mitigating the risk of incomplete or biased definitions of hip-hop feminism. It further proposes three robust theoretical frameworks to comprehensively define hip-hop feminism.